Enhancement techniques for tuberculosis slide images: A review - Nurul Wahidah, M. F.; Mohd Yusoff, Mashor, Prof. Madya. Dr.; Siti Salwa, Md Noor (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/